A Comparison of the Effectiveness of Social-Emotional Competence and Mindfulness Training in Improving the Academic Vitality of Adolescent Girls - Nezakati Hashemian , Hamideh Sadat; Mahdian , Hossein; Bakhshipour , Abolfazl (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The present study aimed to compare the effectiveness of social-emotional competence and mindfulness training in improving the academic vitality of adolescent girls. Methods: The research had a semi-experimental type with a pretest-posttest design, a control group, and a follow-up phase, and its statistical population consisted of adolescent girls studying in the second-grade high schools of district 7 of Mashhad in the academic year of 2020. Among them, 45 girls with lower scores in academic vitality were selected as the samples and randomly assigned to two experimental groups and a control group (15 per group). The first experimental group received the social-emotional competence training package by Larsen and Samdal (2007, 2008) and the second experimental group received the mindfulness training package by Van San et al. (2011) in eight 90-minute weeks. All three groups were evaluated at the three stages, pre-test, post-test, and follow-up, using the academic vitality questionnaire by Hossein Chari and Dehghanizadeh (2012). In this research, the multivariate and univariate repeated-measures analyses of variance were used considering the intragroup (experimental) and intergroup (group membership) factors to investigate the inter-group differences. Results: The social-emotional competence and mindfulness training increased academic vitality in female students (P=0.05). Furthermore, there was no significant difference between the effectiveness of social-emotional competence and mindfulness training on academic vitality (P>0.05). Conclusion: social-emotional competence and mindfulness training were effective in improving academic vitality and there was no difference between their effectiveness.